Tertiary English-majored Students’ Perceptions toward the Role of Pronunciation in English Language Learning and their Practicing Strategies = Nhận thức về vai trò của phát âm tiếng Anh và chiến lược luyện tập phát âm của sinh viên chuyên ngành tiếng Anh - Phan, Gia Thinh, (Đại học Quốc gia Hà Nội, 2020)
Accurate pronunciation has a vital role in English language learning as it can help learners to avoid misunderstanding in communication. However, EFL learners in many contexts, especially at the University of Phan Thiet, still encounter many difficulties in pronouncing English correctly. Therefore, this study endeavors to explore Englishmajored students’ perceptions towards the role of pronunciation in English language learning and examine their pronunciation practicing strategies (PPS). It involved 155 English-majored students at the University of Phan Thiet who answered closed-ended questionnaires and 18 English-majored students who participated in semi-structured interviews. The findings revealed that students strongly believed in the important role of pronunciation in English language learning; however, they sometimes employed PPS for their pronunciation improvement. Furthermore, the results showed that participants tended to use naturalistic practicing strategies and formal practicing strategies with sounds, but they overlooked strategies such as asking for help and cooperating with peers. Such findings could contribute further to the understanding of how students perceive the role of pronunciation and their PPS use in the research’s context and other similar ones.